Regional Economic Outlook, October 2020, Sub-Saharan Africa : A Difficult Road to Recovery. (International Monetary Fund, 2020)
Sub-Saharan Africa is struggling to navigate an unprecedented health and economic crisis-one that, in just a few months, has jeopardized decades of hard-won development gains and upended the lives and livelihoods of millions.